Financial fragility in natural resource-rich economies: Is liberalization a threat? - Kucukoglu, Sami; Genc, Elif Guneren (The Economics and Finance Letters, 2025)
This paper investigates the key drivers of financial fragility in high-income resource-rich economies over the period 2006-2023. The paper uses panel data for 10 high-income, resource-rich countries for the period 2006-2023 and analyzes the interaction between the new CAMEL-based Financial Fragility Index and indicators of financial liberalization, institutional quality, and fiscal stance through a fixed effects model with country fixed effects and estimated with Driscoll-Kraay robust standard errors. The study finds that strong institutions, defined by rule of law safeguards, an independent judiciary, and reliable contract enforcement, support long-term stability. Productively oriented public spending, supported by liquid and well-capitalized banks, reduces macro financial fragility. In contrast to orthodox prescriptions, premature or excessive liberalization creates a paradoxical situation and increases fragility. Rich natural resources alone do not guarantee financial stability; financial stability can be achieved together with institutional strength, prudent budget management, and gradual financial liberalization. Politicians should first strengthen legal and regulatory capacity, then gradually deepen financial markets, and finally accelerate economic diversification that will reduce commodity dependency. Gradual and staged reforms reduce cyclical fluctuations and transform natural wealth into inclusive, sustainable growth.